Professional sport in the Republic of Croatia during the Covid-19 crisis - Smokvina, V.; Ribaric Smokvina, P. (Pravni vjesnik : casopis za pravne i društvene znanosti Pravnog fakulteta Sveucilišta J.J. Strossmayera u Osijeku, 2021)
The paper aims at analysing Croatian professional sport and the impact of the COVID-19 crisis on it. Football was taken as a model for other team sports because of the share of professional sports clubs in the Republic of Croatia in football. In addition, the legal framework set in football may apply to other sports for successfully developing a similar pattern. The analyses are conducted into the revenues (sponsorships, ticketing and TV rights), and expenses (expenses on behalf of players remuneration) of the football clubs in the First Croatian Football League, providing an overview of the professional status of sports clubs, athletes and coaches. It also encompasses an analysis into measures taken by the Government of the Republic of Croatia to support Croatian sport during the COVID-19 crisis. The COVID-19 crisis has been taken as a possible starting position for better regulation of sports in future, especially as regards the professional sports in the Republic of Croatia contributing significantly to the promotion of the Republic of Croatia worldwide.